Understanding the prospects of training industry in Bangladesh and activities of Professional Advancement Bangladesh Limited (PABL) - Tasnim, Zarin (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2020.